2023
DOI: 10.59958/hsf.6681
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the Lipoprotein(a) to Prealbumin Ratio and of the NT-proBNP to LVEF Ratio for Major Adverse Cardiovascular Events Following Percutaneous Coronary Intervention in Patients with Acute Coronary Syndrome

Yingqian Zhang,
Fangyuan Shi

Abstract: Objective: To investigate the lipoprotein(a) [Lp(a)] to prealbumin (PA) ratio and the N-terminal pro-brain natriuretic peptide (NT-proBNP) to left ventricular ejection fraction (LVEF) ratio for the prediction of major adverse cardiovascular events (MACE) in patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). Methods: A 1:1 matched case-control study was performed to retrospectively analyze ACS patients who underwent PCI from January 2022 to June 2022. Patients with MACE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In patients with acute myocardial infarction, the degree of myocardial injury is important to evaluate the therapeutic effect and prognosis, and LVEF is an important indicator to reflect the degree of myocardial injury. Clinical studies have shown that LVEF reduction is one of the risk factors for poor prognosis [22,23]. Decreased LVEF indicates that the left ventricular systolic function is decreased and the heart's ability to pump blood is weakened, which may lead to poor patient prognosis and increased readmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute myocardial infarction, the degree of myocardial injury is important to evaluate the therapeutic effect and prognosis, and LVEF is an important indicator to reflect the degree of myocardial injury. Clinical studies have shown that LVEF reduction is one of the risk factors for poor prognosis [22,23]. Decreased LVEF indicates that the left ventricular systolic function is decreased and the heart's ability to pump blood is weakened, which may lead to poor patient prognosis and increased readmission rate.…”
Section: Discussionmentioning
confidence: 99%